2014
DOI: 10.1016/j.cell.2014.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Interaction Networks as a Means for Singular Olfactory Receptor Expression

Abstract: Summary The transcriptional activation of one out of ~2800 olfactory receptor (OR) alleles is a poorly understood process. Here, we identify a plethora of putative OR enhancers and study their in vivo activity in olfactory neurons. Distinguished by an unusual epigenetic signature, candidate OR enhancers are characterized by extensive interchromosomal interactions associated with OR transcription and share the similar pattern of transcription factor footprints. In particular, we establish the role of the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
260
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(282 citation statements)
references
References 64 publications
8
260
3
2
Order By: Relevance
“…This type of analysis, in combination with 3C, has also been done on the Shh locus at the same stage of limb development (see below) (54) and has been used for visualizing the colocalization of a single olfactory receptor allele and an enhancer element in individual sensory neurons (55). More recently, the Lomvardas laboratory identified the colocalization of multiple putative enhancers with individual olfactory receptor (OR) alleles by chromosome conformation capture-on-chip (4C) and 3D-FISH and determined by Hi-C that many of these colocalizations occurred in trans, which was also confirmed by FISH (56). Each olfactory sensory neuron expresses only one of ϳ2,800 olfactory receptor alleles, and by generating a DNA FISH probe that simultaneously detected most OR loci, this group showed that the silent OR alleles converge to form exclusive heterochromatic foci in a cell type-specific and differentiation-dependent manner (57).…”
Section: Visualizing Genome Organizationmentioning
confidence: 99%
“…This type of analysis, in combination with 3C, has also been done on the Shh locus at the same stage of limb development (see below) (54) and has been used for visualizing the colocalization of a single olfactory receptor allele and an enhancer element in individual sensory neurons (55). More recently, the Lomvardas laboratory identified the colocalization of multiple putative enhancers with individual olfactory receptor (OR) alleles by chromosome conformation capture-on-chip (4C) and 3D-FISH and determined by Hi-C that many of these colocalizations occurred in trans, which was also confirmed by FISH (56). Each olfactory sensory neuron expresses only one of ϳ2,800 olfactory receptor alleles, and by generating a DNA FISH probe that simultaneously detected most OR loci, this group showed that the silent OR alleles converge to form exclusive heterochromatic foci in a cell type-specific and differentiation-dependent manner (57).…”
Section: Visualizing Genome Organizationmentioning
confidence: 99%
“…At finer scales, physical interactions between promoter-distal sites appear to be widespread (Fullwood et al 2009;Sahlén et al 2015;Ghavi-Helm et al 2014;Phillips-Cremins et al 2013) and might function to provide specificity and robustness to enhancer-promoter interactions within cis-regulatory units (Ing-Simmons et al 2015;Markenscoff-Papadimitriou et al 2014). Previous work suggests that enhancer elements tend to cluster in the nuclear space in a cohesin-dependent manner (IngSimmons et al 2015), but how enhancer-enhancer interactions are modulated by extracellular signaling remains largely unknown.…”
Section: Tpo-responsive Enhancers Are Spatially Clusteredmentioning
confidence: 99%
“…In addition, many other types of regulatory sequences, including insulators and Polycomb response elements, may function more efficiently when paired or clustered (reviewed by Bantignies and Cavalli 2011;Herold et al 2012). In non-Dipteran organisms, where somatic homolog pairing is the exception rather than the rule, interchromosomal interactions between nonhomologous sequences are routinely uncovered in whole-genome interaction assays (LiebermanAiden et al 2009;Duan et al 2010;Sexton et al 2012;van de Werken et al 2012;Nagano et al 2013;Zhang et al 2013), and specific trans-interactions have been linked to several examples of gene regulation (Spilianakis et al 2005;Bacher et al 2006;Xu et al 2006;Apostolou and Thanos 2008;Sandhu et al 2009;Markenscoff-Papadimitriou et al 2014;Patel et al 2014). Thus, it appears that interchromosomal communication is adaptable to the different global principles for genome organization present in Dipteran and non-Dipteran organisms and likely plays a role in maintaining correct patterns of gene expression across diverse species.…”
Section: Does Transvection Play a Role In The Wild?mentioning
confidence: 99%
“…In contrast, the genetic impacts of trans-interactions between chromosomes are less clearly understood. Examples of gene regulation involving interchromosomal associations have been described (Spilianakis et al 2005;Bacher et al 2006;Xu et al 2006;Apostolou and Thanos 2008;Sandhu et al 2009;Markenscoff-Papadimitriou et al 2014;Patel et al 2014), but it remains unclear whether it is common for sequences that regulate gene expression to communicate between different chromosomes when they are physically juxtaposed.In Drosophila melanogaster, extensive trans-interactions are observed between homologous chromosomes in virtually all somatic tissues, a phenomenon known as somatic homolog pairing (reviewed by McKee 2004;Bosco 2012). The close proximity of homologous chromosomes in Drosophila can permit an enhancer to act in trans on a promoter on the paired homolog, a form of pairing-dependent gene regulation called transvection (Lewis 1954).…”
mentioning
confidence: 99%
See 1 more Smart Citation